Monoclonal Antibodies Bind a SNP-Sensitive Epitope that is Present Uniquely in Mycobacterium avium subspecies paratuberculosis - John P Bannantine; Judy eStabel; Elise eLamont; Robert E Briggs; Srinand eSreevatsan (Frontiers in Cellular and Infection Microbiology, 2011)
Due to a close genetic relatedness, there is no known antibody that detects M. avium subspecies paratuberculosis (MAP), which causes Johne’s disease in cattle and sheep, and does not cross-react with other M. avium subspecies. In the present study, a monoclonal antibody (17A12) was identified from mice immunized with a cell membrane fraction of MAP strain K-10. This antibody is 100% specific as it detected a 25-kDa protein in all 29 MAP whole cell lysates, but did not bind to any of the 29 non-paratuberculosis strains tested in immunoblot assays. However, the antibody revealed variable reactivity levels in MAP strains as it detected higher levels in bovine isolates but comparably lower levels in ovine isolates of MAP. In order to identify the target binding protein for 17A12, a lambda phage expression library of MAP genomic fragments was screened with the monoclonal antibody. Four reactive clones were identified, sequenced and all shown to be overlapping. Further analysis revealed all four clones expressed an unknown protein encoded by a sequence that is not annotated in the K-10 genome and overlapped with MAP3422c on the opposing DNA strand. The epitope of 17A12 was precisely defined to 7 amino acids and was used to query the K-10 genome. Similarity searches revealed another protein, encoded by MAP1025, possessed a similar epitope (1-amino acid mismatch) that also reacted strongly to the antibody. A single nucleotide polymorphism (SNP) in MAP1025 was then identified by comparative sequence analysis, which results in a Pro28His change at residue 28, the first amino acid within the 17A12 epitope. This SNP is present in all MAP strains but absent in all non-MAP strains and accounts for the specificity of the 17A12 antibody. This new antibody is the first ever isolated that binds only to the paratuberculosis subspecies of M. avium and opens new possibilities for the specific detection of this significant ruminant pathogen.